A systematic review and meta-analysis on pharmacist-led interventions for the management of peptic ulcer disease. - Biswash Sapkota; Bipindra Pandey; Bishal Sapkota; Keshav Dhakal; Bijay Aryal (PLoS ONE)
Pharmacists are essential for developing pharmacotherapy plans, conducting clinical assessments, and overseeing drug monitoring. Their interventions help prevent medication errors and adverse drug events and enhance medication safety. This study aimed to systematically review pharmacist-led interventions for managing medication-related issues in patients receiving anti-ulcer treatments. A systematic review and meta-analysis was performed to explore four databases for studies published from 1904 up to June 2024. Nine studies were reviewed, including four retrospective, three case-control, one mixed-method, and one prospective pre-post study involving 34,099 participants. The average age of the patients was 61 years, and 50.23% were male. The study quality was high, with an average score of 6.22/7 on the modified Newcastle-Ottawa scale. All studies involved direct interactions between pharmacists and patients or physicians, and data were primarily collected from hospital electronic records. Pooled analysis demonstrated that pharmacist interventions significantly improved the rational use of anti-ulcer medications (OR: 4.5; 95% CI: 0.97 to 20.80; I2 =  89%, P =  0.05), as reported by studies. Pharmacist interventions have a significant impact on improving rational drug use, reducing costs and treatment duration, and enhancing appropriate medication use. These interventions also positively influenced medication adherence and the correction of irrational drug use.